Analisis Kinerja Keuangan Bank Syariah Indonesia Berdasarkan Rasio Profitabilitas, Likuiditas, dan Efisiensi Tahun 2021–2024 - Febriansyah, Fandi; Faiqoh, Elok (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2025)
Bank Syariah Indonesia (BSI) plays a strategic role in maintaining national economic stability, especially after the merger in 2021. Structural changes resulting from the merger require an evaluation of financial performance to assess BSI's ability to maintain profitability, liquidity, and operational efficiency amid increasingly fierce industry competition. This study aims to analyze BSI's financial performance during the 2021–2024 period using quantitative analysis methods on annual financial reports with ROA, ROE, FDR, and BOPO ratios. The results show a positive and consistent trend: ROA increased from 1.61% to 2.49% and ROE from 13.71% to 17.77%, reflecting an increase in asset and capital efficiency. FDR rose from 73.39% to 84.97%, indicating optimization of intermediary functions, while BOPO decreased from 80.46% to 69.93%, indicating improved operational efficiency. These improvements illustrate the success of the post-merger integration strategy, which has strengthened BSI's financial structure and competitiveness in the national market. These findings also confirm that BSI is able to maintain stable financial performance in a sustainable and adaptive manner to macroeconomic dynamics.